The Effect of Teacher Professional Development and School Management on Teacher Performance in Senior High Schools - Utami, Wiwik; Putra, Alhadi Yan; Pahlawan, Pahlawan (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
Teacher performance is a key determinant of instructional quality and school effectiveness. However, previous studies have often examined teacher professionalism and school management separately, resulting in limited empirical evidence on their combined effects, particularly in the context of senior high schools at the district level. This study aims to examine the influence of teacher professional development and school management on teacher performance, both partially and simultaneously. A quantitative explanatory design with multiple linear regression analysis was employed. The population consisted of 80 teachers, all of whom were included as the sample using total sampling. Data were collected through Likert-scale questionnaires that met validity and reliability requirements and analyzed using SPSS. The results indicate that teacher professional development (β = 0.549; p < 0.001) and school management (β = 0.386; p < 0.001) have positive and significant effects on teacher performance. Simultaneously, both variables explain 72.7% of the variance in teacher performance (R² = 0.727; p < 0.001). These findings highlight the importance of synergy between individual professional capacity and effective school management.